Transformasi Digital UMKM Studi Kasus Strategi Adopsi Teknologi - Wulandari, Ayu; Dompak, Timbul; Salsabila, Lubna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to investigate the technology adoption strategy by MSMEs in Batam City in facing digital transformation. The research problem discusses the importance of technology mastery for MSMEs and the challenges and opportunities faced in adopting digital technology. The research method used is descriptive qualitative through participatory observation and in-depth interviews with MSME actors. The study results show that education, training, and collaboration are the main strategies for strengthening MSMEs' technology adoption. Education and training help MSMEs understand the potential of technology to increase efficiency and competitiveness, while collaboration with various parties provides access to the necessary resources and support. In conclusion, investment in technology mastery and building collaboration is the key to the growth and sustainability of MSMEs in this digital era, enabling them to develop and compete in an increasingly complex and competitive market. Keywords: Transformation, Digital, MSMEs